THE MAIN ASPECTS OF HYPERTEXT TECHNOLOGY AS A CONCEPTUAL MODEL OF INFORMATION STRUCTURING - Kadirov Mirjalol Tolmasovich (American Journals, 2023)
Currently, modeling is of a general scientific nature and is used in the study of living and inanimate nature, in the sciences of Man and society.The main purpose of scientific models is to explain the sum of information related to the subject of knowledge. Therefore, it would be wrong to see the main purpose and function of the model only as a means of obtaining information about the prototype. Explaining an object using its model means gaining new knowledge about it.
Keywords: Model, modeling, hypertext, links, interactivity, information systems, interconnection, data structure construction.